PARADIGMA PEMBANGUNAN EKONOMI DESA, ONE PERSON ONE PRODUCT, ONE VILLAGE ONE PRODUCT, ONE VILLAGE ONE CORPORATION: Array - Gunawan Sumodiningrat; Hastangka (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2021)
Villages are an important part of the country. The progress of a country is determined by the progress of the village. The village is an important measurement tool in national development. Ironically, the village has not received much attention either from the government or from other stakeholders. The purchasing power and selling power of people in rural areas is still minimal in developing the quality of life of the community. Currently, the paradigm of village economic development is only seen from the aspects of infrastructure and physical development. However, the paradigm of village economic development has not been seen much in terms of the quality of life of the community is guaranteed, the village is independent and sustainable, as well as the welfare of body and soul. The problem of village development has so far been focused on economic growth and improvement. This is a gap in the village. The purpose of this research is to explore and explore the paradigm of village economic development based on One Person One Product, One Village One Product, One Village One Corporation. This research method by conducting theoretical studies and field studies conducted in Yogyakarta. The results of this study and research indicate that the village economic development paradigm needs to form a frame of mind in laying the village economic development paradigm